IDENTIFICATION OF WHEAT GERMPLASM RESISTANT TO LEAF, STRIPE AND STEM RUST USING MOLECULAR MARKERS - Alma Kokhmetova; Makpal Atishova; Kanat Galymbek (Scientific Journal of Pedagogy and Economics, 2020)
Wheat leaf rust, stripe and stem rust are major wheat diseases in Kazakhstan that reduce yield and quality and cause considerable economic damage. This study utilized winter wheat germplasm from different national and international nurseries to evaluate their value for genetic and breeding programs directed towards improvement of wheat rust resistance in Kazakhstan. Based on the data from field experiments, the most valuable sources, combined resistance to both leaf and stripe rust were 16 lines and cultivars (28.6%), including mainly entries from CIMMYT and IWWIP. Nineteen entries (30.6%) had high level of resistance to leaf rust in the field tests. Thirty-three entries (53%) were effective to control stripe rust. In our study 22% wheat accessions studied had polymorphic band linked to leaf rust resistance gene Lr10. Based on rust reactions and data of molecular analysis, 3% entries were found to have Lr19/Sr25, 11% entries – Lr26/Sr31/Yr9/Pm8, 43% entries – Lr34/Yr18, 12% entries – Lr37/Yr17/Sr38, 17% – Lr68 gene and 6% entries – Yr10 gene. Only one line from IWWIP nursery showed presence of Yr15 gene. Out of 38 studied entries, the fragment of DNA associated with Sr22 gene in 13 wheat entries observed. Gene Sr22 was identified in five Kazakhstani and in 8 Belarusian wheat entries. The results obtained used for developing wheat cultivars resistant to rust.